SOCIAL ACTIVITY OF STUDENTS ON THE BASIS OF PEDAGOGICAL NEOLOGY (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article covers in detail the issues of improving the social activity of students on the basis of pedagogical neonology in the system of higher education.